Participation and Intermediary NGOs - World Bank (Washington, DC, 2012)
Nongovenrmental organizations (NGOs) can be effective intermediaries in Bank funded projects which depend on participation and capacity building at the community level. Successful collaboration depends on identifying an organization with appropriate characteristics, and involving its staff in decisionmaking from as early as possible in the project cycle. Steps must be taken to prevent Bank or government requirements undermining the participatory orientation of the NGO and, where necessary, to strengthen NGO capacity, encourage cooperation between NGOs, and support communication between NGOs and government.